2006
DOI: 10.1258/136218006779160607
|View full text |Cite
|
Sign up to set email alerts
|

Hysterectomy and sexual function

Abstract: Hysterectomy is one of the most common major gynaecological operations performed in the UK and the USA. Its impact on sexual function is a major cause of preoperative anxiety. Unfortunately, this anxiety is seldom articulated by patients, nor recognized and discussed by clinicians. Reports about the impact of hysterectomy on sexual function have been conflicting, partly due to the use of different and often unsatisfactory parameters to assess sexual function. The aim of this review is to assess the current evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 33 publications
1
33
1
8
Order By: Relevance
“…Reports on the impact of hysterectomy on sexual function have been conflicting, with some evidence of improvement after hysterectomy [11,12] but also of sexual impairment [13].…”
Section: Discussionmentioning
confidence: 99%
“…Reports on the impact of hysterectomy on sexual function have been conflicting, with some evidence of improvement after hysterectomy [11,12] but also of sexual impairment [13].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of sexual function is a major cause of anxiety for women scheduled for hysterectomy. 30 Indeed, physician education is critical to mitigate this stress; a recent study showed that education about possible negative sexual outcomes predicted overall satisfaction with hysterectomy. 31 Unfortunately, despite the significance of this issue, the literature is not consistent or clear.…”
Section: Hysterectomymentioning
confidence: 99%
“…Los posibles cambios en la función sexual (FS) tras la histerectomía (HT) inquieta y genera ansiedad a las mujeres que han de pasar por dicha intervención quirúrgica 1,2 . De hecho, dos estudios encontraron que el potencial deterioro de la función sexual después de esta cirugía es una de las causas de inquietud, previas a la intervención, más frecuentes 2,3 .…”
Section: Introductionunclassified
“…En un intento de resolver dichas dudas, se han realizado y publicado multitud de revisiones y estudios sin llegar a ninguna conclusión, ya que algunos de ellos deducen que la histerectomía no provoca cambios en la sexualidad de la mujer [9][10][11][12][13] , otros que la mejora 1,[14][15][16]6 mientras que otros encuentran un deterioro de la misma 3,4,12,[16][17][18][19] .…”
Section: Introductionunclassified